2021
DOI: 10.3390/su13041936
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Sustainability of the Intermediary Role in Blockchain

Abstract: Traditional business models involve cost, market development, distribution channels, business partnerships, and supply chain management. The development of the digital economy and digital network technology has engendered a shift away from the traditional model of operation. Intermediaries have long played an essential role in promoting the benefits of economic activities, but new technology is increasingly replacing intermediaries in their roles of connecting players, such as, involving, committing, and mobil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 24 publications
0
26
0
Order By: Relevance
“…The well-being of a society is predicated on some elements like fairness, ethics, human rights, and diversity acceptance. Some previous studies (e.g., [26][27][28][29][30]) examined how blockchain helps to maintain social sustainability. For example, the recent case studies by Tseng and Shang [55] indicated that the blockchain's features of security, immutability, resiliency, auditability, and permissibility render trust and antitampering among the blockchain users.…”
Section: Literature About Impact Of Blockchain In Supply Chainsmentioning
confidence: 99%
See 2 more Smart Citations
“…The well-being of a society is predicated on some elements like fairness, ethics, human rights, and diversity acceptance. Some previous studies (e.g., [26][27][28][29][30]) examined how blockchain helps to maintain social sustainability. For example, the recent case studies by Tseng and Shang [55] indicated that the blockchain's features of security, immutability, resiliency, auditability, and permissibility render trust and antitampering among the blockchain users.…”
Section: Literature About Impact Of Blockchain In Supply Chainsmentioning
confidence: 99%
“…Wang, Jie and Abareshi [80] illustrated how blockchain enables transparency as any transaction updates will be propagated to the parties (e.g., delivery company, manufactory, and stock management department) in the blockchain network. Once the transactions are approved by all the involved parties in the blockchain network, the transaction records stored at all the parties are immutable, facilitating the verification processes among the parties for auditing [29], achieving cost efficiency by eliminating unnecessary intermediaries and so reducing transaction costs [29], and enabling traceability of transactions [11,81,82]. The case study in Park and Li [11] demonstrated how Wal-Mart has achieved traceability using blockchain technology and improved the process of tracking the food delivery from a supplier to a consumer.…”
Section: Literature About Applicability Of Blockchain In Supply Chainsmentioning
confidence: 99%
See 1 more Smart Citation
“…The dimensions are interrelated and are defined according to Wut et al as follows: environmental sustainability (environmental) is defined as "the continuous preservation of the ecosystem and its functions; economic sustainability means the lasting ability of the economic system to meet all human needs and social sustainability promotes the well-being of all people; such as access to food, medicine, education and recreation [14]. Overall, sustainability aims to protect our natural environment and human health, while promoting the balance of ecosystems and innovation, and economic behavior must be improved in the interests of human and environmental sustainability; for this purpose, technological innovation is a support tool [15]. Wut et al also defines digital sustainability, which in the narrower sense is the sustainable use of digital resources (data and computer files, source codes and technologies) -the ability of a digital system to be constantly maintained, resp.…”
Section: Sustainability Of Digital Technologiesmentioning
confidence: 99%
“…Blockchain-based cloud server architecture sells their extra storage capacity to renters, and they made payments through blockchain with proper security and trust. The world economic forum's survey predicted that by 2027 world GDP might be store 10% on blockchain infrastructure (C. Te Tseng & Shang, 2021). Due to blockchain infrastructure, secure service provisioning and safe edge computing devices are possible for end-users.…”
Section: Introductionmentioning
confidence: 99%